THE RIGHT TO LIBERTY AND SECURITY: A PRECONDITION FOR ESTABLISHING AND GUARANTEEING THE HUMAN SECURITY - Besim Kusar (European Scientific Journal, ESJ, 2015)
In most democratic countries public order is a constitutional category, within which the state has the power for the rule of law, justice, intelligence agency, civil emergency agencies and border control. In this context security institutions protect the public security and the rights of all citizens. The right to liberty and security is a precondition for establishing and guaranteeing the human security. If by ‘Public Order’ we mean respect for law and for the public institutions by the citizens, then within public peace and order we should mean also the protection of legal interest and liberty of citizens. According to this definition, the object of public order would encompass the respect for laws by the citizens; respect for public institutions by the citizens; protection of legal interest by the state institutions; protection of the rights of citizens by the state institutions. Public order is also the biggest legal guarantee for human security since public order includes all legal norms which are consumed by the people in order to make them feel that the human security they have been searching for all their life, lies in their homes, workplace and in public. All issues related to the dynamics of the communities enter the area of human security, but this is applicable for the entire community and not just for an individual. Thus, the public order balances the needs and wishes of individuals for a bigger area for movement and activities, which results in guaranteeing the individual security within the security in the community.